Plasma zinc concentration in cord blood and associated factors of infant birth weight among mothers who delivered in Fatemieh Hospital, Hamadan, Iran - Nazari, Mojgan (2012)
Micronutrient deficiency is one of the most prevalent nutritional problems all over the world, especially in the developing countries. Nowadays, more than 2 billion persons are deprived of getting the minimum micronutrients intake needed for health. Zinc is an essential trace element that has an important role in normal growth and development. Zinc deficiency during pregnancy may have an adverse effect on pregnancy outcome, especially low birth weight (LBW) and some malformation such as cleft palate and anencephaly. The World Health Organization reported that 20 million infants were born with LBW in 2008. LBW increases the risk of infant mortality. The goal of the millennium development goals (MDG) until 2015 is to reduce child mortality. The objective of this study was to determine the analysis of plasma zinc concentration in cord blood and associated factors of infant birth weight among mothers who delivered in Fatemieh Hospital, Hamadan, Iran using the case-control study design. The cases were healthy infants  2500 g and the controls were healthy infants >2500 to 4000 g at time of birth. A total of 268 (134 cases, 134 controls) infants and their mothers were selected at the time of birth at the Fatemieh teaching hospital which admits high risk mothers and has a neonatal intensive care unit (NICU) ward in Hamadan, Iran. The data collection of this study started from 6tl December 2009 and ended on 18th October 2010. Cord blood zinc was collected at the time of delivery from venous cord blood Plasma zinc concentration was determined by Atomic Absorption Spectrophotometry (AAS) method. Data was analyzed using SPSS version 16. Total of 268 mothers infant pair participated in the study about zinc level in the cord blood among these mothers, 3.7% had severe zinc deficiency, 7.8% had mild to moderate zinc deficiency and 88.5 % had normal plasma zinc concentration. The independent sample t-test showed that there was no significant difference between plasma cord blood zinc among LBW and normal birth weight infants ( t= -0.083, P-value= 0.934) at the P level of 0.05. The mean birth weight among low birth weight infant (LBW) was 2267.5 ± 324 g and in normal infants was 3311± 323 g. The meal gestational age in LBW and normal infants were 35.85 ± 3 and 39 ± 1.4 weeks, respectively. There was a significant association between the plasma cord blood zinc concentration in LBW and normal weight infants (X2 (df: 2) = 6.934, P=0.031). Hierarchical multiple logistic regressions showed that plasma cord blood zinc, maternal pre-pregnancy BMI, maternal weight gain during pregnancy, maternal age, previous LBW, and parity significantly predicted infant birth weight. Overall, there was no statistically significant relationship between plasma cord blood zinc concentration and infant birth weight. Infants with severe zinc deficiency (S 60 g /dl) were more than 12 times at higher risk of LBW compared to infants with normal plasma cord blood zinc levels (OR = 12.234,95% CI 1.22, 133.39, P= 0.040). In conclusion, there was a significant association between severe zinc deficiencies in plasma cord blood and infant birth weight. There was also significant association between maternal pre-pregnancy BMI, maternal weight gain during pregnancy, maternal age, previous history of LBW, and parity with infant birth weight.